Does Indigenous Knowledge Occur in and Influence Impact Assessment Reports? Exploring Consultation Remarks in Three Cases of Mining Projects in Greenland - Dahl, Parnuna Petrina Egede; Hansen, Anne Merrild (Arctic Review on Law and Politics, 2019)
Mineral extraction is pursued in Greenland to strengthen the national economy. In order that new industries promote sustainable development, environmental impact assessments and social impact assessments are legally required and undertaken by companies prior to license approval to inform decision-making. Knowledge systems in Arctic indigenous communities have evolved through adaptive processes over generations, and indigenous knowledge (IK) is considered a great source of information on local environments and related ecosystem services. In Greenland the Inuit are in the majority, and Greenlanders are still considered indigenous. The Inuit Circumpolar Council stresses that utilizing IK is highly relevant in the Greenland context. Impact assessment processes involve stakeholder engagement and public participation, and hence offer arenas for potential knowledge sharing and thereby the utilization of IK. Based on the assumption that IK is a valuable knowledge resource, which can supplement and improve impact assessments in Greenland thus supporting sustainable development, this paper presents an investigation of how IK is utilized in the last stages of an impact assessment process when the final report is subject to a hearing in three recent mining projects in Greenland.